Michael D. Cox letter to Thomas H. Kent regarding captured and banded raptors, November 17, 1993 - Cox, Michael D.et al (1993)
Letter from Michael D. Cox to Thomas H. Kent regarding captured and banded raptors, November 17, 1993. Cox details the various types of raptors that were caught and banded during fall migration by the Iowa State University Wildlife Care Clinic. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1993. Plustek - flatbed